2017
DOI: 10.1038/ijir.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

Time-course changes of nLDL-induced erectile dysfunction

Abstract: Hyperlipidemia is an important risk factor for atherosclerosis and is frequently seen in patients with erectile dysfunction (ED). This study was designed to evaluate whether the acute effect of native low-density lipoprotein (nLDL) on intracavernosal pressure (ICP) is reversible and related to plasma asymmetrical dimethylarginine (ADMA), endogenous inhibition of endothelial nitric oxide synthase (eNOS) levels and eNOS expression in cavernous tissues. Hyperlipidemia was induced by a single dose of intravenous 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The same finding was observed in cross-sectional studies included in a literature review conducted in 2009 [ 24 ]. Likewise, similar reports demonstrated that hyperlipidaemia was a significant risk factor for developing ED among this group of patients across the globe [ 34 37 ]. In contrast to this finding, one study documented a non-significant relationship between ED and dyslipidaemia among males with DM in Sri Lanka [ 7 ].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The same finding was observed in cross-sectional studies included in a literature review conducted in 2009 [ 24 ]. Likewise, similar reports demonstrated that hyperlipidaemia was a significant risk factor for developing ED among this group of patients across the globe [ 34 37 ]. In contrast to this finding, one study documented a non-significant relationship between ED and dyslipidaemia among males with DM in Sri Lanka [ 7 ].…”
Section: Discussionmentioning
confidence: 61%
“…The significant association may reflect the negative effects of hyperlipidaemia on the vascular smooth muscle tissue of the penis and the peripheral cavernous nerve [ 38 , 39 ]. Moreover, hyperlipidaemia-induced impairments in erectile functions might be related to an increase in plasma asymmetrical dimethylarginine levels, changes in the regulation of the endothelial nitric oxide synthase (eNOS) levels, and eNOS expression in cavernous tissues [ 37 ]. Additionally, one study revealed that different statin types might have different effects on erectile dysfunction [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We showed that LDL‐C and HDL‐C are associated with arteriogenic erectile dysfunction which confirmed the majority of previous studies, although different parameters were adopted. LDL‐C can cause endothelial dysfunction of the penile artery and induce erectile dysfunction in mice . The accumulation of sub‐endothelial lipids, especially low‐density lipoproteins, plays an important role in initiating endothelial dysfunction and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…17e19 Hyperlipidemia not only causes damage to the vascular smooth muscle tissue of the penis but it also can induce ED by causing damage to the peripheral cavernous nerve that innervates a penile erection. 19,20 It has been extensively studied that autophagy was shown to regulate lipid droplet degradation directly. 13 In our study, it was found, on the basis of MET, that there was improvement in FPG, HbA1c, and AGEs and that ICA II could regulate lipid metabolism by increasing HDL levels and decreasing LDL, TC, and TG levels in T2DMED rats.…”
Section: Discussionmentioning
confidence: 99%
“…17 It has been shown that downregulation of the NOS and cGMP-phosphodiesterase activities are an important occurrence in the pathogenesis of ED. 20,21 Serum T is the main component of androgen and plays a key role in maintaining male sexual function. 22 E2 can resist androgen action in vivo.…”
Section: Discussionmentioning
confidence: 99%